2019
DOI: 10.15446/acag.v68n3.69127
|View full text |Cite
|
Sign up to set email alerts
|

Yield and popping expansion components in local popcorn varieties from Southern Brazil

Abstract: The aim of this study was to evaluate grain yield (GY), popping expansion (PE), popping expansion disregarding the weight of unpopped kernels (PEW), and eleven other agronomic and morphological traits of 14 local popcorn varieties (LPV) from far west of the state of Santa Catarina, Southern Brazil. Two experiments were carried out, in a completely randomized block design with three replications, in different regions of Santa Catarina: one in the municipality of Florianópolis (east coast) and the other in Anchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The values obtained for the thickness/width ratio and CCI of LP were 0.62 (0.39-1.01) and 0.27 (0.18-0.48), respectively. By studying popcorn landraces in southern Brazil, Gonçalves et al (2019) and Seledes et al (2019) reported CCI values between 0.28-0.30 and 0.27-0.35, respectively; and between 0.60-0.82 for the thickness/width ratio observed by Gonçalves and colleagues. These indices indicate the rounded shape of the grains and have a positive correlation with the expansion capacity.…”
Section: Physical Properties Of the Lpmentioning
confidence: 86%
See 3 more Smart Citations
“…The values obtained for the thickness/width ratio and CCI of LP were 0.62 (0.39-1.01) and 0.27 (0.18-0.48), respectively. By studying popcorn landraces in southern Brazil, Gonçalves et al (2019) and Seledes et al (2019) reported CCI values between 0.28-0.30 and 0.27-0.35, respectively; and between 0.60-0.82 for the thickness/width ratio observed by Gonçalves and colleagues. These indices indicate the rounded shape of the grains and have a positive correlation with the expansion capacity.…”
Section: Physical Properties Of the Lpmentioning
confidence: 86%
“…A (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i8.17141 close value was observed for some LP grains (0.48). More productive ears contain a greater number of grains, and consequently have less space for grain growth, interfering with their shape (Gonçalves et al, 2019). This observation may be a hypothesis that would justify the variation in grain size and shape observed in the LP, in addition to the heterogeneity characteristic of landraces.…”
Section: Physical Properties Of the Lpmentioning
confidence: 95%
See 2 more Smart Citations
“…Pordesimo, Anantheswaran, Fleischmann, Lin, & Hanna (1990), working with five varieties of popcorn, found a strong correlation between circularity and expansion capacity (r = 0.87), concluding that small, short and wider grains, with higher values of circularity, presented higher values of expansion. In the work of Gonçalves, Mayer, Souza, & Ogliari (2019), the authors found values from 0.24 to 0.32 for the circularity character of three popcorn cultivars. In that work, a positive correlation between circularity and expansion was also observed.…”
Section: Discussionmentioning
confidence: 96%